2017
DOI: 10.1007/s00441-017-2717-6
|View full text |Cite|
|
Sign up to set email alerts
|

Laminin-derived Ile-Lys-Val-ala-Val: a promising bioactive peptide in neural tissue engineering in traumatic brain injury

Abstract: The adult brain has a very limited regeneration capacity and there is no effective treatment currently available for brain injury. Neuroprotective drugs aim to reduce the intensity of cell degeneration but do not trigger tissue regeneration. Cell replacement therapy is a novel strategy to overcome brain injury-induced disability. To enhance cell viability and neuronal differentiation, developing bioactive scaffolds combined with stem cells for transplantation is a crucial approach in brain tissue engineering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 122 publications
0
19
0
Order By: Relevance
“…For OPCs, various integrin dimers with the β 1 subunit have been found to promote survival, regulate a switch from proliferation to differentiation and mediate myelination by mature oligodendrocytes . Several studies have found that inclusion of IKVAV peptides in hydrogel‐type biomaterials increased neuronal differentiation of transplanted NS/PCs after traumatic brain injury . Inclusion of IKVAV has also been reported to reduce astrogliosis after injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For OPCs, various integrin dimers with the β 1 subunit have been found to promote survival, regulate a switch from proliferation to differentiation and mediate myelination by mature oligodendrocytes . Several studies have found that inclusion of IKVAV peptides in hydrogel‐type biomaterials increased neuronal differentiation of transplanted NS/PCs after traumatic brain injury . Inclusion of IKVAV has also been reported to reduce astrogliosis after injury .…”
Section: Discussionmentioning
confidence: 99%
“…97,98 Several studies have found that inclusion of IKVAV peptides in hydrogel-type biomaterials increased neuronal differentiation of transplanted NS/PCs after traumatic brain injury. 99 Inclusion of IKVAV has also been reported to reduce astrogliosis after injury. 100,101 In vitro, IKVAV-bearing hydrogels are reported to promote differentiation of neurons while reducing differentiation of astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…They also participate in early embryonic development and organogenesis. Laminins and laminin-derived peptides are successfully used for enrichment of biomaterials [38,75,82,83].…”
Section: Lamininsmentioning
confidence: 99%
“…Another important integrin binding ligands come from laminins. Thus, IKVAV (Ile-Lys-Val-Ala-Val) and YIGSR (Tyr-Ile-Gly-Ser-Arg) are considered as the most promising pro-adhesive motifs [38,75,82,83].…”
Section: Peptidesmentioning
confidence: 99%
“…The desirable properties of a scaffold for stem cell transplantation are biocompatibility, biodegradability, mimic the 3D biological microenvironment, incorporation of different ECM, pore size, stability, electrical conductivity, porosity, non-immunogenicity, interconnectivity, safety (low or non-toxic) and alignment[ 70 , 76 , 77 ]. Various fabrication techniques have been developed to produce different scaffolds, such as emulsion freeze-drying, electrospinning, thermally-induced phase separation, solvent casting/particular leaching, computer-aided design/computer-aided manufacturing, melt molding, rapid prototyping (3D printing, selective laser sintering, stereolithography, and fused deposition modeling), nanofiber self-assembly, and photolithography[ 78 , 79 ].…”
Section: Different Types Of Scaffold Formulationsmentioning
confidence: 99%